Risk Factors for Long‐Term Coronary Artery Calcium Progression in the Multi‐Ethnic Study of Atherosclerosis. Issue 8 (August 2015) - Gassett, Amanda J.; Sheppard, Lianne; McClelland, Robyn L.; Olives, Casey; Kronmal, Richard; Blaha, Michael J.; Budoff, Matthew; Kaufman, Joel D.
Abstract : Background: Coronary artery calcium (CAC) detected by noncontrast cardiac computed tomography scanning is a measure of coronary atherosclerosis burden. Increasing CAC levels have been strongly associated with increased coronary events. Prior studies of cardiovascular disease risk factors and CAC progression have been limited by short follow‐up or restricted to patients with advanced disease. Methods and Results: We examined cardiovascular disease risk factors and CAC progression in a prospective multiethnic cohort study. CAC was measured 1 to 4 times (mean 2.5 scans) over 10 years in 6810 adults without preexisting cardiovascular disease. Mean CAC progression was 23.9 Agatston units/year. An innovative application of mixed‐effects models investigated associations between cardiovascular disease risk factors and CAC progression. This approach adjusted for time‐varying factors, was flexible with respect to follow‐up time and number of observations per participant, and allowed simultaneous control of factors associated with both baseline CAC and CAC progression. Models included age, sex, study site, scanner type, and race/ethnicity. Associations were observed between CAC progression and age (14.2 Agatston units/year per 10 years [95% CI 13.0 to 15.5]), male sex (17.8 Agatston units/year [95% CI 15.3 to 20.3]), hypertension (13.8 Agatston units/year [95% CI 11.2 to 16.5]), diabetes (31.3 Agatston units/year [95% CI 27.4 to 35.3]), and other factors. Conclusions: CAC progression analyzed over 10 years of follow‐up, with a novel analytical approach, demonstrated strong relationships with risk factors for incident cardiovascular events. Longitudinal CAC progression analyzed in this framework can be used to evaluate novel cardiovascular risk factors.